PERLINDUNGAN HUKUM PEMEGANG POLIS TERHADAP GAGAL BAYAR PERUSAHAAN ASURANSI JIWASRAYA (STUDI KASUS: PUTUSAN 589/PDT.G/2019/PN.JKT.PST) - Vera W.S Soemarwi; Evelin Wiyasih (Jurnal Hukum Adigama, 2022)
This study discusses Decision Number 589/PDT.G/2019.PN.JKT.PST the judge's consideration who didnot accept the lawsuit regarding the Jiwasraya policyholder on the grounds of not including the bank. Theproblems are: 1) Can a third party outside the insurance company be drawn as a party who is alsoresponsible for the implementation of the policy payment obligations issued by PT Asuransi Jiwasraya(Persero)? 2) How is the policy holder's legal protection against insurance company defaults in terms of theConsumer Protection Act and POJK No. 1 of 2013 concerning Consumer Protection in the FinancialServices Sector? 3) How is the status of the policy in terms of government programs? The a-quo decisionwas analyzed by the author using normative legal research methods. The results showed that the thirdparty, namely the bank and OJK, could not be drawn as the party responsible for implementing theachievements of PT Asuransi Jiwasraya (Persero). The bancassurance agreement was made between thebank and Jiwasraya with the approval of the OJK. The OJK's responsibility for the implementation ofachievements cannot be included because of the OJK's responsibility as a regulator and the responsibilityof the insurance company supervisor. Through this case, it can be said that UUPK and POJK No. 1 of 2013has not provided legal protection to insurance consumers. The government's efforts to restructure thepolicy have harmed policyholders, both those who agree with the restructuring and those who do not. ifJiwasraya were to restructure, then Jiwasraya should not have harmed the policyholders. If the policyholder does not agree with the policy restructuring, it is obligatory to announce the value set by Jiwasraya.